2016
DOI: 10.1002/chin.201627222
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Structure Revision of Caesalpinistas A and B and Isolation of a New Furanoditerpenoid from the Cotyledons of Caesalpinia decapetala var. japonica.

Abstract: The new diterpenoid, deoxycaesaljaponin A (I) is isolated along with the known caesalpinista B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Ficus nipponica is a wild evergreen climbing plant native to Southeast Asia, bearing a fig‐like fruit with a diameter of 10 mm. During a continuing search for biologically active compounds from plants, we found that the crude MeOH extract of the fruits of F . nipponica showed antibacterial activity against Bacillus subtilis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ficus nipponica is a wild evergreen climbing plant native to Southeast Asia, bearing a fig‐like fruit with a diameter of 10 mm. During a continuing search for biologically active compounds from plants, we found that the crude MeOH extract of the fruits of F . nipponica showed antibacterial activity against Bacillus subtilis .…”
Section: Introductionmentioning
confidence: 99%
“…Ficus nipponica is a wild evergreen climbing plant native to Southeast Asia, bearing a figlike fruit with a diameter of 10 mm. During a continuing search for biologically active compounds from plants, [10] [11] we found that the crude MeOH extract of the fruits of F. nipponica showed antibacterial activity against Bacillus subtilis. Bioassay-guided fractionation of the crude extract led to the isolation of two new prenylated ortho-dihydroxycoumarins, designated as fipsomin (1) and fipsotwin (2), together with a known prenylated coumarin, apigravin (3).…”
Section: Introductionmentioning
confidence: 99%